Odpowiedzi

2009-12-17T19:26:39+01:00
A) (3x+2)² = 3(3x²+5)
9x²+12x+4=9x²+15
9x²+12x-9x²=15-4
12x=11 |:12
x=11/12
b) 3x(3x-4) = (3x-2)²
9x²-12x=9x²-12x+4
9x²-12x-9x²+12x=4
0x=4
c) (½x-2)²+ x = O.25x(x-8)
1/4x²-2x+4+x=1/4x²-2
1/4x²-2x+x-1/4x²=-4-2
-x=-6
x=6

d) (O,09y-3,6)y = (2-0,3y)²
0,09y²-3,6y=4-1,2y+0,09y²
0,09y²-3,6y+1,2y-0,09y²=4
-2,4y=4
y=-1,(6)

a) 4x-(x-6)² > x(5-x) +5x
4x-(x²-12x+36)>5x-x²+5x
4x-x²+12x-36-5x+x²-5x>0
6x>36
x>6

x nalezy (6;∞)

b) (2x+4)² < 2x(3+x) +2x²+6
4x²+16x+16<6x+2x²+2x²+6
4x²+16x-2x²-2x²-6x<6-16
10x<-10
x<-1

x nalezy (-∞:-1)